Predicting the responses of boreal forests to climate-fire-vegetation interactions in Northeast China. (July 2022) - Huang, Chao; Feng, Jiayuan; Tang, Fangran; He, Hong S.; Liang, Yu; Wu, Mia M.; Xu, Wenru; Liu, Bo; Shi, Fuxi; Chen, Fusheng
Abstract: Climate change could alter species composition, with feedback on fire disturbances by modifying fuel types and loads. However, the existing fire predictions were mainly based on climate-fire linkages that might overestimate the probability and size of fire disturbances due to simplifying or omitting vegetation feedback. We applied a model-coupling framework that combines forest succession, climate-fire linkages, and vegetation feedback to predict burned area, aboveground biomass, and species composition of boreal forests in Northeast China under climate change conditions. Results showed that climate change and fire would favor the recruitment of deciduous species, but these species need a long-time to replace the existing coniferous species. Burned area would increase with climate change. Climate change, historical and future fire disturbances affect aboveground biomass by altering tree mortality and regeneration. Further studies should address strategies for altering species composition through forest management practices to adaptation climate change and reduce carbon losses from fire. Graphical abstract: Image 1 Highlights: We applied a model-coupling framework to simulate the response of boreal forest to climate-fire-vegetation interactions. Climate change and fire would favor the recruitment of drought-tolerant species. Climate change would significantly increase the burned area of boreal forests. Climate change, historical and future fire disturbance would affect aboveground biomass of boreal forests. It is necessary to implement forest management strategies to alter species composition for reducing burned area and carbon losses from catastrophic fires.